Analysis of Student Knowledge Test Results of Teacher Professional Education Study Program (PPG) Teacher Training Personnel Education Institution (LPTK) UIN Bukittinggi - M, Iswantir; Sesmiarni, Zulfani; Iltavia, Iltavia; Nurzuliana Rashed, Zetty; Septi Asih, Redha (BiCED Proceeding, 2023)
This research aims to measure the level of learning achievement of students in the Teacher Professional Program knowledge test for each subject in 2021 at LPTK UIN Bukittinggi (PPG). This research is a qualitative descriptive study. This research was conducted at the Professional Teacher Study Program (PPG) Faculty of Tarbiyah and Teacher Training LPTK UIN Bukittinggi. The subjects of this research were 75 PPG LPTK UIN Bukittinggi students who had not yet graduated from UP. Consideration of research subjects is based on the results of the 2021 UKMPPG Knowledge Test which is only held by each student who has not passed the Knowledge Test (UP) which is distributed to the LPTK. Of the 75 PPG participants who were declared not to have passed the Knowledge Test (UP) in 2021, we only collected 73 people in this study. Because the 2 people did not take the Knowledge Test (UP) because there was a natural disaster in their home environment and there was 1 person who did not want to continue PPG activities. Based on the results and discussion of the research, it can be concluded as follows, that first; PPG student knowledge test results in 2021 were lowest in CP 3 and highest in CP 1. Second; The lowest percentage of PPG participant scores in 2021 is in the very good criteria and the highest is in the fair criteria.